If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 7 = 18x + -4 Reorder the terms: 7 + 7x = 18x + -4 Reorder the terms: 7 + 7x = -4 + 18x Solving 7 + 7x = -4 + 18x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-18x' to each side of the equation. 7 + 7x + -18x = -4 + 18x + -18x Combine like terms: 7x + -18x = -11x 7 + -11x = -4 + 18x + -18x Combine like terms: 18x + -18x = 0 7 + -11x = -4 + 0 7 + -11x = -4 Add '-7' to each side of the equation. 7 + -7 + -11x = -4 + -7 Combine like terms: 7 + -7 = 0 0 + -11x = -4 + -7 -11x = -4 + -7 Combine like terms: -4 + -7 = -11 -11x = -11 Divide each side by '-11'. x = 1 Simplifying x = 1
| 0=(.2-x)*(.0002-3x)*(.0002-3x)*(.0002-3x) | | x=3+0.25y | | x=3+0.25y | | 3(15)+5=5(15)-25 | | -1/3=5 | | e/6=12/4 | | 12/4=d/8 | | (z+8)(z-11)= | | -9(x-9)=(x+63) | | t=14 | | -3(1)=3 | | 10y+20x=130 | | 9x^2-18xy+8y=0 | | x+3/5=2 | | c+3/5=2 | | 18+a=16 | | 2*3x+11=6x+4 | | 9-v^2=0 | | 5/4.5=-7.18 | | y/9+7=4(y-7) | | y^2-6x-11=0 | | u^2-1u-2=0 | | (4-u^2)=0 | | 1=-3x+3 | | 6x^2-19x-3=0 | | -(9-m)=-(6m+9) | | 4x+y=112 | | d/5=100-4 | | 2(2)+3y=13 | | 17/3-x/4=4x | | 117=0.25*x | | -3(t-4)+8t=3t-2 |